STUDI PENELUSURAN TERHADAP KOMPETENSI KEILMUAN LULUSAN PROGRAM STUDI PMI FAKULTAS DAKWAH DAN KOMUNIKASI UIN AR-RANIRY DI DUNIA KERJA - Misbah, T. Lembong; Zulfadli, Zulfadli (JURNAL AL-IJTIMAIYYAH, 2018)
The competencies of graduates of PMI study programs are very important, especially in the Social Service and Community Empowerment Service. Therefore research is needed on the study of scientific competencies of graduates of PMI Faculty of Da'wah and Communication at UIN Ar-Raniry in the world of work. So this kajin formulates information sources in the context of work, stakeholders, and supporting skills in supporting work professionalism. This qualitative research collects data by conducting evaluations, surveys, interviews and documentation. The results of the study found that social work was still not finished by workers from social worker backgrounds. PMI graduates' competencies are currently adequate and good, but there needs to be an increase and development of self-capacity. The supporting skills needed by graduates of PMI's study program are to improve the scientific field of work, to be mediated, to master information technology, even as graduates of the Da'wah and Communication Faculty of UIN Ar-Raniry must be able to practice religious values and be sufficient role models in the workplace. Keywords: Competence, Science, PMI, World of Work